Understanding Smart Environment Strategy in Developing Countries Cities - Tulungen, Franky Reintje; Batmetan, Johan Reimon (JR Education, 2022)
A smart environment is a necessity in many modern cities when information technology becomes the choice of communication and interaction. The purpose of this research is to formulate a proposed strategy that is measurable and easy to operate in implementing a smart environment in cities in developing countries. We use a competitive intelligence approach to build a smart environment strategy. The results of this study, we formulate a smart environment strategy in cities whose countries are developing based on the smart city model in one of its dimensions, namely the smart environment dimension. We formulate Strategic Alignment by making a mapping based on the mission and goals of city leaders to the dimensions of the smart environment. We also conducted a gap analysis using SWOT analysis and developed a smart city implementation strategy with 4 categories, namely strategic, key operational, high potential, and support